Estilos de aprendizaje y su incidencia en el rendimiento académico de los estudiantes - Asimbaya Barahona, Juan Gabriel (2017)
The research is focused on learning styles, to determine the involvement in the application in the teaching process learning and its impact on the achievement of students of basic education school "Dr Luis Eguiguren" in Amaguaña parish, Quito canton, Pichincha province during the first and second Quimestre of the academic year 2016-2017. Which has 16 teachers, methodology is one type training, having as a purpose to disseminate existing information in behalf of the development of the capacities of key learning for the formation of the research, applied techniques are the survey, obtaining the following conclusion abaut learning styles which should be considered as an important aspect in the process of teaching, learning and its relationship with academic achievement , since the learning styles are not taking into account by teachers as a tool, but it is important that you use in the teaching-learning process….